CLIL Instructions in Indonesian Tertiary Tourism Study Program: An Analysis of Students’ Perceptions - I Putu Edi Sutrisna (International Journal of Instructions and Language Studies, 2023)
CLIL instructions in many countries were proven to be beneficial for its effects on the students’ learning achievement both on content of subject matters as well as the English competence. However, in South East Asian setting, especially in Indonesia, there was a limited study exploring about what the students perceived about CLIL instructions.  Therefore, the present study administering quantitative survey research with cross-sectional design aimed at analyzing the Indonesian tourism tertiary students’ perception on CLIL instructions. The sample of study was 219 students attending tourism study program from four universities in Bali, Indonesia. The data was collected through administering validated questionnaire to the sample of the study. Data analysis was done by using descriptive statistical analysis to summarize data from the findings in this survey research. The results of present study found out that Indonesian tourism tertiary students perceived CLIL instructions positively. Therefore, it was suggested that CLIL was suitably be implemented in a vocational program such as in tourism study program to help students build domain-specific knowledge of both content and the target language through meaningful learning activities.